(untitled) (Research, Society and Development, 2024)
Objective: To investigate medical students’ knowledge about HIV pre-exposure prophylaxis (PrEP). Methodology: An analysis was carried out with the answers of 290 students from the University of Vassouras, in the state of Rio de Janeiro, enrolled in the periods from the first to the twelfth. The answers were collected during the second academic period of 2023, through an electronic form with 12 questions, made available via Google Forms, accompanied by a Free and Informed Consent Form. The project was previously submitted to Plataforma Brasil and to the institutional ethics committee, obtaining approval under opinion 5.966.511. Results: Analyzing the performance according to the academic cycle, in the basic cycle of the 127 participants, 62.2% of them had <50% of correct answers. The clinical cycle with 133 answers presented 66.91% with a correct level of less than 50%. Of the 30 participants in the internship, 66.67% got <50% right. Conclusion: From the above, it is possible to observe that most of the answers by specific groups obtained a yield of less than 50% of correct answers. In view of this, it is evident that there is a need to implement additional measures to address the identified gaps, such as the inclusion of specific classes on PrEP in the mandatory curriculum of medical school, as well as the regular holding of voluntary events to reinforce the importance and consolidate knowledge on the subject. However, due to the scarcity of studies in this area, it is challenging to determine an ideal success rate. Therefore, it is hoped that this study can guide the development of strategies to improve students’ knowledge about PrEPs.